The Influence of Cultural Adaptability, Digital Knowledge Management and Organizational Support on Digital Leadership Capability in E-Commerce Companies - Sidjabat, Sonya; Hendratni, Tyahya Whisnu; Violin, Vivid; Mustafa, Fahrina; Kusnadi, Iwan Henri; Lubis, Alifah Lettiane Virainy (Yayasan Gema Bina Nusantara, 2026)
Digital leadership abilities which help organizations succeed in all aspects of technological development should become mandatory requirements for e-commerce workers. The study assesses how cultural adaptability and digital knowledge management and organizational support systems together influence e-commerce organizations to develop their digital leadership capabilities. The research uses a quantitative methodology which follows an explanatory study framework. The researchers used purposive sampling to gather data from 160 participants who worked at e-commerce businesses throughout Indonesia. The researchers used multiple linear regression analysis to assess the data after they finished validating their findings and testing all reliability and classical assumptions. The research shows that digital leadership performance improves through the combination of cultural adaptability and digital knowledge management together with organizational support systems. The research proves that organizations need to establish an adaptive organizational culture which includes technology-based knowledge management together with complete organizational support to develop their digital leadership skills. The research results deliver strategic guidance to e-commerce businesses which want to build digital leadership capabilities that will endure longer periods.